Vessel-Sourced Pollution: A Security Threat In Malaysian Waters - Abdul Kader, Sharifah Zubaidah Syed; Abdulrazaq, Abdulkadir O. (Journal of Sustainable Development Law and Policy, 2025)
Vessel- sourced pollution is one of the major sources of marine pollution and it encompasses accidental discharge of oil, intentional discharge of oil (like discharge from ballast tanks), chemicals, dumping, etc. The United Nations Convention on the Law of the Sea (UNCLOS), 1982 and some other conventions make provisions concerning protection of marine environment and this has the support of many other regional, national and global institutions. In Malaysia, the consent of the relevant authority is required for a discharge of oil that is above the quantity allowed under the law. However, despite the fact that there have been enormous regulations on the pollution of the marine in Malaysia, it appears that pollution by vessels is still on the increase. The legal framework stipulating conditions for discharge of oil at seas are well founded in many jurisdictions like Malaysia but some of the legal regulation appears to be inadequate, thereby threatening sea’s environment and causing the irreparable damage to marine resources and human safety. This paper considers the number of ships that traverse the straits of Malacca and the implications of pollution arising therefrom. It recommends for consent of the appropriate authority and a stiffer penalty for every discharge of oil by vessel in order to avert hazardous damage arising from pollution by ships.